Export Incentives, Financial Constraints, and the (Mis)Allocation of Credit : Micro-level Evidence from Subsidized Export Loans - Zia, Bilal H. (2012)
This paper combines an exogenous shock to the supply of subsidized credit with unique loan-level data from the export sector in Pakistan to identify the impact and allocation of such financial incentives. The removal of subsidized credit causes a significant decline in the exports of privately owned firms, while the exports of large, publicly listed, and group network firms are unaffected. Publicly listed firms make no significant adjustments to their balance sheets, and only their profits are reduced, indicating that they are financially unconstrained. Nearly half of all subsidized loans are assigned to such firms, implying a substantial misallocation of credit and an output loss to privately owned firms of 0.75% of GDP. Productivity differences do not explain the heterogeneous effects across firms.